Kindness begins with yourself: The role of self‐compassion in adolescent body satisfaction and eating pathology. Issue 7 (12th April 2019) - Pullmer, Rachelle; Coelho, Jennifer S.; Zaitsoff, Shannon L.
Abstract: Objective: A wealth of evidence indicates that self‐compassion is linked with positive psychological outcomes; however, little is known about the process through which self‐compassion exerts its effect. The primary purpose of this research was to investigate the direct and indirect impact of self‐compassion on body satisfaction and eating pathology in adolescents. Method: Two hundred and thirty‐eight students were recruited from three local high schools ( M age  = 16.49, 43.7% boys). All participants completed the Self‐Compassion Scale (SCS), Hopkins Symptom Checklist (SCL‐5), Body Areas Satisfaction Scale (BASS), and Eating Disorder Examination Questionnaire ‐ Adolescent Version (EDE‐Q) at baseline. The SCL‐5, BASS, and EDE‐Q were completed 4 months later. Results: Self‐compassion was positively associated with body satisfaction and negatively associated with psychological distress and eating pathology in boys and girls at both time points. Longitudinal conditional process analyses revealed that self‐compassion predicted changes in body satisfaction and eating pathology through changes in psychological distress for girls only. Notably, self‐compassion was higher in boys than in girls. Discussion: Results underscore how self‐compassion may be an important factor to target in fostering a positive body image and preventing disordered eating in adolescents.